Stock Market Prediction using Machine Learning: A Systematic Literature Review - Vadlamudi, Siddhartha (American Journal of Trade and Policy, 2017)
Different machine learning algorithms are discussed in this literature review. These algorithms can be used for predicting the stock market. The prediction of the stock market is one of the challenging tasks that must have to be handled. In this paper, it is discussed how the machine learning algorithms can be used for predicting the stock value. Different attributes are identified that can be used for training the algorithm for this purpose. Some of the other factors are also discussed that can have an effect on the stock value.